Cece loves science - Derting, Kimberly; Johannes, Shelli R. (Greenwillow Books, an imprint of HarperCollinsPublishers, 2018)
Cece, a budding and inquisitive scientist, and her equally curious best friend Isaac conduct experiments to see whether Luna's dog Einstein will eat his vegetables.